Exploration of Local Potential: Economic Transformation and Empowerment of MSME In Bakalankrajan, Malang City - Sajida, Sajida; Toriquddin, Muhamad; Taborat, Aloysius; Ester Putri Carolline Gea (Prosiding Seminar Nasional Pengabdian Masyarakat Universitas Ma Chung, 2024)
The economic dynamics in RW 05 and 06 Bakalankrajan, Malang City, have found new light through an innovative strategy that combines halal certification with the integration of digital technology. MSMEs in this region are the main focus, with the aim of strengthening the foundations of the local economy and increasing their competitiveness in the global market. Through a multidisciplinary approach, the empowerment program explores local potential and encourages broader market penetration with halal certification. In line with this, E-Commerce training provides additional tools for MSMEs to seize opportunities in the increasingly developing digital realm. With an inclusive approach and data-driven strategy, the project foresees a significant transformation in the local economic landscape. The hope is that this effort can create a new pattern of economic empowerment for local communities and provide encouragement for sustainable growth in RW 05 and 06 Bakalankrajan.